A Union Member's Perspective on Technological Change - Cunningham, Bart; Hull, Dennis (Relations industrielles / Industrial Relations, 1988)
After having defined some of concerns union members have with technological change, this paper outlines the recent history of such changes in the telecommunications industry before offering a viewpoint on future responses to the issue.